Readability of Discourse of Productive Textbooks in Indonesian Language for Class XI Erlangga Publishers Based on Fry's Graphic Formula - Syarah Khairat; Rian Hidayat (UIR Press, 2022)
Textbooks are one of the components used as learning resources. With textbooks, teachers can find out the material to be studied or studied by students, so that it can make it easier for teachers to choose the learning method used so that learning objectives can be achieved properly. For students, textbooks are used as learning resources in independent learning activities and can be used to repeat and review material that has been delivered by the teacher. Textbooks have a lot of discourse as an introduction to a material in learning. The discourse should be read and understood by students according to their school level. A good discourse is a discourse whose material can be read or understood by students. Therefore, to find out that discourse can be read well by students, it is necessary to measure the level of readability of textbooks. The level of readability of a text can be measured in various ways or methods, one of which is the Fry graph formula. Fry's graphic formula is a readability measurement based on the length of a short sentence whose measurement does not involve the reader. This study uses a sample of discourse in the Indonesian Language Productive textbook for class XI SMK publisher Erlangga.